KARAKTERISASI KARBON PELET CAMPURAN RUMPUT GAJAH (Pennisetum purpureum Scumach) DAN TEMPURUNG NYAMPLUNG (Calophyllum inophyllum Linn.) - Santiyo Wibowo; Daniel P.O Laia; Mohammad Khotib; Gustan Pari (BRIN Publishing, 2017)
Carbon pellet is a charcoal product made from carbonized biomass which is crushed into fine powder and compacted into pellet. Carbon pellets is designed for renewable energy alternatives for cooking, the combustion process and the possibilities for steam power plants as a substitute for coal. This paper studies the quality of carbon pellet made from a mixture of elephant grass with nyamplung shell. After carbonization, the elephant grass and nyamplung seed shell were crushed into 60 mesh powder for pellet with various ratio of elephant grass charcoal and nyamplung shell charcoal namely 100:0, 75:25, 50:50, 25:75, and 0:100 homogenously. Ten percent PVAC adhesive was added into the mixture prior to compression. Results show that the mixture composition of 75% elephant grass charcoal and 25% nyamplung shell charcoal is recommended for carbon pellet. The mixture composition improved physical properties with the average of 3.35% water 3 content, 26.19% volatile matter, 13.59% ash content, 60.21% carbon bound, 0.68 kg/cm density, 5.91 kg/cm compressive strength and calorific value of 6080 cal/g.